Influence of Social Media Usage on the Academic Performance of Arabic Students in Tertiary Institutions in Katsina State, Nigeria - Bilkisu Muhammad Abusufiyan; Binta Bello Malumfashi; Habiba Abubakar Daura; Muhammad Bala Muhammad (International Journal on Integrated Education, 2023)
This study investigated the influence of social media usage on the academic performance of Arabic students in tertiary institutions of Katsina state. The investigation was carried out with a researcher designed questionnaire. A total of 248 students were selected using Stratified random sampling technique. Data collected were analyzed with the Statistical Package for the Social Sciences (SPSS), IBM version 26. Statistical procedure adopted included descriptive statistics. The Chi-square was used to determine the extent of association at the fixed alpha level of 0.05. Findings revealed that WhatsApp, Facebook, Tiktok, Instagram, Telegram, Twitter and Linkedin in order of hierarchy were the social media being used by the students. It was found that Arabic students accessed their social media at anytime, anywhere but with more emphasis on during free time and when at home and that social media are generally used for academic, social connections, news and other information such as trending gist, clothing style, music among others. Use of WhatsApp and Facebook were found to manifest addictiveness among the students. Students were of the view that social media improve on their academic performance. Use of social media except Facebook was not significantly associated with students’ gender but use of Facebook was found to be significantly associated with students’ gender. Indulgence in use of social media was found to be associated with a number of challenges which included unsolicited information often encountered in the internet, among others. It was recommended, among others that since it was reported that Social media has positive influence on Arabic student’ academic performance, Curriculum development stakeholders should include Social media as part of the strategies for the implementation of the Nigeria’s educational curriculum.